Trabalho de reprodução social para o Sistema Prisional Cearense - Sales, Ana Carolina Nunes de Macedo (2023)
This research aims to analyze the labor dispensed by women as a result of the incarceration of a loved one, considered here as a type of social reproductive labor. This work aligns with contemporary Social Reproduction Theory (SRT), by understanding that categories of oppression are co-produced with the production of surplus value simultaneously. The present analysis was conducted through an online patchwork ethnography approach, examining dialogues taken from a Facebook group called Mulheres de Presos (“Prisioner’s Women”), during the Covid-19 pandemic successive lockdowns, and it has taken into account women’s engagement on government penal institutions’ social media, specially Instagram, as well. A judge, a public defender (both with experience in criminal matters) and a woman, whose partner was incarcerated, were interviewed in order to highlight different perspectives regarding their contact with prisons and complement previous observations. This study focuses on the labor invested in producing those who have been incarcerated, emphasizing, on one hand, the State’s costs and, on the other hand, the activities operated by families. It was found that these women, though these online platforms, especially Facebook, were able to build networks of solidarity and information sharing, including their “reviews” of the establishments' administrations and some legal advices stemming from their own personal experiences with the judicial system. The pandemic revealed the lack of access to information and the many activities carried out by families for the State. Therefore, these women shared experiences that demonstrated how families which are affected by the punitive policies of the State find themselves in an ambivalent position of burden and resistance.